2001
DOI: 10.1159/000052986
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Hyaluronan with a Hyaluronan-Specific Hyaluronic Acid Binding Protein in the Placenta in Pre-Eclampsia

Abstract: Hyaluronan (HA), a high molecular weight polysaccharide, is a major component of connective tissue and is thus present in the extracellular matrix of most tissues. Increased serum concentrations have been reported in association with pre-eclampsia and liver malfunction, amongst other disorders. We have performed histochemical investigations with a HA-specific hyaluronic acid binding protein in placentas from uncomplicated pregnancies and from patients with pre-eclampsia. Staining for HA was found in the stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…HA appears to be expressed on the syncytiotrophoblast surface [108,183], and constitutes approximately 1%-2% of glycosaminoglycans in extracts of placental blood from uninfected placentas [3]. One study suggested that the expression of HA is low in normal placentas, but markedly increased in inflammatory conditions such as pre-eclamptic toxemia [108].…”
Section: Hyaluronic Acid (Hyaluronan)mentioning
confidence: 99%
See 1 more Smart Citation
“…HA appears to be expressed on the syncytiotrophoblast surface [108,183], and constitutes approximately 1%-2% of glycosaminoglycans in extracts of placental blood from uninfected placentas [3]. One study suggested that the expression of HA is low in normal placentas, but markedly increased in inflammatory conditions such as pre-eclamptic toxemia [108].…”
Section: Hyaluronic Acid (Hyaluronan)mentioning
confidence: 99%
“…One study suggested that the expression of HA is low in normal placentas, but markedly increased in inflammatory conditions such as pre-eclamptic toxemia [108]. This may suggest that HA is not a major receptor for initiating parasite sequestration, but could augment adhesion of HA-binding parasites as inflammation develops.…”
Section: Hyaluronic Acid (Hyaluronan)mentioning
confidence: 99%
“…Furthermore, hyaluronic acid and its binding proteins are used in studies as a method for evaluation of hyaluronan localization in the placenta in pre-eclampsia [6] or a supplementation in improvement of oocyte meiotic capability [7]. The interaction between spermatozoa and hyaluronic acid, which depends on sperm maturity and remodeling of the sperm plasma membrane during spermiogenesis, is also another feature that has been used to design the hyaluronic acid binding assay (HBA) [8].…”
Section: Introductionmentioning
confidence: 99%
“…There is one comparable study performed by Matejevic et al who observed hyaluronic acid in the fetal vessel walls (tunica intima, media, and adventitia), but the authors unfortunately did not refer to the endothelium. 8 For heparan sulfate, the third major component of the EGX examined in the current study, only minimal traces of reaction products could be detected on the STL and none on fetal endothelia. Again no relevant difference existed between patients with HELLP and healthy women.…”
mentioning
confidence: 47%